Awareness, Treatment and Control of High Blood Pressure during a Screening Session in Porto-Novo - SONOU, Arnaud; WANVOEGBE, FINANGNON ARMAND; HOUENASSI, DÈDONOUGBO MARTIN (My University, 2018)
Background: The purpose was to determine the level of awareness, treatment and control of high blood pressure (HBP) in the gen- eral population in Porto-Novo (Benin). Materials and Methods: A descriptive cross-sectional study was conducted in the city of Porto-Novo. During a screening of HBP, people have voluntarily presented for the measurement of their arterial blood pressure (BP). HBP was defined in all subjects with BP > 140/90 mmHg or who had a history of hypertension under medication. A controlled hypertension was defined in the case of BP < 140/90 mmHg under medical treatment. Results: 267 subjects aged 43 ± 16.3 years were included, with a sex ratio of 0.98. The prevalence of HBP was 59.5%; 39.2% had a known history of hypertension (66.7% above 60 years and 59% were women); 43.9% of those with HBP were unaware of their condition; good adherence to drug therapy was found in 28.6% of patients and was associated with advanced age. The proportion of controlled HBP was 20.7%. Conclusion: These results demonstrate the need of actions for primary prevention of hypertension and for the reduction of the num- ber of HBP diagnosis made at the complication stage.
Keywords: Hypertension; Awareness; Treatment; Control; Porto-Novo